FORECASTING AND DECISION-MAKING VIA USE OF STATISTICAL LAWS OF RANDOM ECONOMIC INDICATORS - Victor A. Vlasov; Sergey I. Alexeev; Raisa I. Soroka; Andrey O. Tolokonski (Статистика и экономика)
The article shows that the estimation (forecasting) of the values of random variables, according to the minimum variance estimation error is not always effective, and sometimes not even possible. The authors give examples to prove it. The estimation is described with a functional. The task of the estimation is treated as a search for an optimal solution and is illustrated with formation of the optimal playing strategy.